المسح الشامل لتحري نقص خميرة G6PD لدى المولودين حديثاً عند الجنسين في الساحل السوري - يوسف أحمد حسن; محمد سميرة (Latakia University Journal -Medical Sciences Series, 2019)
We have screened 830 newborns in the hospitals of the coastal region in Syria for G-6-PD deficiency within the first 48 hrs of life. There are 27% of boys and 18% of girls were deficient, number of girls was more than expected by Hardy-Weinverg law. The family history for G-6-PD deficiency and the estimation of G-6-PD enzyme in fathers of affected girls suggested that most of the cases are Heterozygous with the normal x chromosome is inactivated by random in activation (Lyon Hypotheses). We proved that Screening for G-6-PD deficiency should include both sexes (males and females). It is a simple way that provides us with an important information about G-6-PD deficiency early enough to put the necessary protective plan. لقد أجرينا مسحاً شاملاً لـ 830 مولوداً حديثاً خلال 48 ساعة من الولادة لتحري نقص خميرة غلوكوز ـ 6 فوسفات، في مشافي المنطقة الساحلية في سورية ووجدنا أن هناك نقصاً في هذه الخميرة لدى 27% من الذكور و18% من الإناث. وعدد الإناث كان أكبر من المتوقع بحسب قانون هاردلي ـ ولينبرغ. القصة العائلية لنقص خميرة غلوكوز ـ 6 فوسفات ومعايرة الخميرة عند أباء الإناث اللواتي لديهن نقص الخميرة تُظهر أن معظم الحالات كانت متخالفة الأمشاج تثبط فيها الصبغي X الطبيعي بالتثبيط العشوائي (نظرية LYON). إن النتائج التي توصلنا إليها تسمح بالقول إنه يجب تطبيق التحري الشامل لكل المولودين حديثاً (ذكور، إناث) حول النقص في هذه الخميرة. لقد أثبتنا أن المسح الشامل من أجل نقص خميرة غلوكوز ـ 6 فوسفات يجب أن يشمل كلا الجنسين الذكور والإناث. وهو طريقة بسيطة تقدم لنا معلومات مهمة حول نقص الخميرة من أجل وضع خطة الوقاية اللازمة.